WAYS OF DEVELOPING THE MARKETING CHANNELS FOR SELLING GRAIN - Vasylyna , О.; Kolach , С. (Bulletin of Lviv National Environmental University. Series "AIC Economics", 2023)
Aggravation of the problems of sales and strengthening of competition, the need to focus on the consumer necessitates each enterprise, including the agricultural one, to develop a sales and marketing concept for its activity. However, the product and production concept still prevails in agriculture that is primarily caused by the shortage of agricultural products, and the mismatch of its supply with the existing demand. Today, the practice recognizes the important role of private households in the formation of the commodity supply of agricultural products. It requires justification of the approaches to optimize the process of building a structure of the distribution channel, determining the composition of its participants, distribution of functions between them, tracking the effectiveness of the channel functioning as well as its participants, coordination of its activity, structure, and composition, i.e. implementation of the distribution channel management. The financial and psychological problems hinder the creation of marketing services at all levels of the economy because marketing research is not conducted, agricultural enterprises are not interested in original marketing developments, and in the end, the accumulated world experience is not promoted. Hence, there is no effective system of domestic agricultural marketing because of the non-system and random individual studies that negatively affect the level of competitiveness of agricultural products. It is noted that agriculture is characterized by its commercial nature, which requires a clear and effective interaction of production and sales of products of economic entities. The article summarizes the peculiarities of the formation of grain sales channels by peasant farms in modern conditions and systematizes the factors that prevent them from becoming full-fledged partners in market relations. The modern structure of sales channels for agricultural products in the domestic market is presented. The study substantiates the directions of the formation of the grain sales channels and determines the expediency of applying the marketing concept.